Conditions and perspectives of financial lending in Macedonian agriculture and rural development - Gjosheva Kovachevikj, Marija; Kovacev, Goran; Risteski, Hristijan (University of East Sarajevo, Faculty of Agriculture, Republic of Srpska, Bosnia, 2013)
Agriculture is a fundamental economic activity in Macedonia which constitutes 10% of GDP over the past decade, adding related processing industry increases this share to approximately 15%-16%. During the last period of economic restructuring, agriculture played a critical role in the social and economic stability of the country. As a generator of growth of income and employment (19% of the total employment) agriculture needs a steady stream of funds to increase the competitiveness of the farmers by improving the technological and market infrastructure as well improving quality of life of rural population. Beside the state financial support of agriculture and rural development, the commercial financing - through lending is from utmost importance as well. The absorption of the available funds by rural population is limited by strong criteria. The pressure for acceleration process for developing of the competitive and sustainable agriculture and sustainable rural communities require better access of the funds to farmers. In this regards, the purpose of the research is to explore the existing situation in the lending system in agriculture and further provide analysis and recommendations for improving the commercial form of financing to farmers. Therefore, the desk work and field research through questionnaire and interviews have been conducted in order to collect information about needs and problems of the key actors in the field of lending in the agriculture and rural development. The results have been communicated with the stakeholders at panel discussion and furthermore upgraded and distributed to the relevant institutions and organisations. Findings demonstrate that the lending system in agriculture does not operate in an ideal environment and its facing numerous problems and obstacles.
Keywords: lending, agriculture and rural development, financial institutions, farmers